Where Do Real Output Shocks to Nigeria Mainly Emanate From? Empirical Analysis of Nigeria-China-India-USA Economic Interactions - Orji, Anthony; Nwodo , Ikenna Paulinus; Ogbuabor, Jonathan E.; Anthony-Orji, Onyinye I. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
This study investigated Nigeria’s economic interactions with China, India, and the USA with a view to identifying the main source of real output shock to Nigeria in the period 1981Q1-2019Q4. The analysis followed the network approach of Diebold and Yilmaz (2014), which uses the size and direction of normalized generalized forecast error variance decompositions (NGFEVD) of a vector error correction model to track shock propagation among economic entities. The results indicate that China and India are net transmitters of real output shocks to Nigeria. The results also indicate that Nigeria is a net real output shock receiver. The study concludes that Nigerian policymakers should evolve policies that can insulate the economy against real output shock heatwaves from around the world, especially China and India. Such policies should mainly target the diversification of the economy such that crude oil will no longer be the only major source of revenue.